Rethinking Gender Mainstreaming in the era of austerity - Alfama, Eva; Cruells, Marta; De la Fuente, Maria (Investigaciones Feministas (Feminist Research), 2015)
This paper address the implications for the Gender Mainstreaming strategy of the present economic and political crisis, at both EU and Spanish level. In the first place the main achievements and shortcomings of the implementation of gender equality policies during the last decades are briefly pointed. Secondly, the gendered dimensions of the crisis are explored: both in the crisis genesis, in its social impacts, as well as in the policies developed to face it. A specific attention is placed in the weakening of the democratic decision-making process in key areas of the current political and economic governance. To conclude we identify the challenges, obstacles and opportunities that this new scenario pose to mainstream gender in policy making, raising some questions regarding the need to rethink the priorities, the courses of action and the tools of equality policies.